Prediksi Tingkat Kriminalitas Menggunakan Metode Single Moving Average (Studi Kasus Polres Asahan Sumatera Utara) - Lubis, Mustopa Husein; Sumijan, S (Jurnal Sistim Informasi dan Teknologi, 2021)
Crime is all kinds of actions and actions that are economically and psychologically harmful that violate the laws in force in the State of Indonesia as well as social and religious norms. Ordinary criminal acts affect the security of the community and endanger their lives and minds. The research location is the Asahan Police which is an agency that can provide security and protection for the community, especially those in Asahan Regency. The problem that occurs in this location is that there is no prediction system in Asahan Regency, due to the lack of knowledge factor in processing crime rate data. So it is difficult to know how much increase or decrease in criminal cases committed at the Asahan Police. The data used is data on cases of murder, sexual monitoring, tracing, violent theft, weight theft, motorcycle theft, fraud and counterfeiting money for the last 5 years in 2016 as many as 2020. Based on these problems, create a system for the crime rate in the Regency. Asahan to anticipate future crimes. The system that will be made uses forecasting or forecasting. With the Single Moving Average forecasting method. The Single Moving Average method is a forecast for the time in the future. The results of the calculation of criminal acts in 2021 found that there were 3 cases of murder, 2 cases of sexual intercourse in 2021, 252 cases of the 2021 return, 27 cases of violent theft in 2021, and 348 cases of bicycle theft in 2021. motorbikes in 2021 which open 90 cases, in 2021 which opens 85 cases, and money counterfeiting in 2021 which opens 1 case.